John Wood 2: Planning and Paying for His Town Plans. (August 2014) - Robson, Brian
<x content-type="archive" xml:space="preserve">Abstract</x> John Wood, the 19th-century urban cartographer, surveyed almost 150 towns spread widely across Great Britain. His detailed large-scale plans are an astounding achievement. In light of this, two questions are posed: did he have a strategy that guided the places which he surveyed; and how did he pay for his work, given that so few copies of his plans appear to have been produced for sale – or at least to have survived.